2009
DOI: 10.4081/or.2009.e5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical excision of wrist ganglia; literature review and nine-year retrospective study of recurrence and patient satisfaction

Abstract: The main options for the treatment of wrist ganglia are reassurance, aspiration, arthroscopic resection and open excision. Variations within each option have been described and the literature is clouded by widespread variability in the results reported. We present the results of our own long-term retrospective study, review the literature and question the surgical risks and demands placed on healthcare resources. A retrospective review of the surgical results of dorsal and volar wrist ganglia excision between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 26 publications
0
28
0
1
Order By: Relevance
“…9 However, in most of the recent publications, a higher incidence of ganglions of the hand and wrist in women is clearly noticeable. [10][11][12][13][14][15][16][17][18] Although this is a well-known fact, no rational grounds for explaining it are available. According to Rollins et al, female patients are also more predisposed to ganglion recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 However, in most of the recent publications, a higher incidence of ganglions of the hand and wrist in women is clearly noticeable. [10][11][12][13][14][15][16][17][18] Although this is a well-known fact, no rational grounds for explaining it are available. According to Rollins et al, female patients are also more predisposed to ganglion recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…19 The incidence of ganglions is 43 per 100,000 in women and 25 per 100,000 in men and, according to some authors, a further upward trend is observed -55 per 100,000 of the population per year. 3,12,14 The mean age of the patients included in our study was 41.3 ± 16.9 years and the median age was 39.5 years. These numbers were undoubtedly influenced by the fact that mainly adult patients are admitted to our ward and pediatric patients only sporadically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that open surgery for a volar ganglion is challenging. 5 The main causes of complications and recurrence are close proximity to the superficial palmar branch of the radial artery and to the palmar cutaneous branch of the median nerve. 6 , 7 Arthroscopic resection of a volar wrist ganglion was originally described by Ho et al 8 To date, one prospective, randomised controlled trial has been conducted to establish which treatment modality provides the lowest rate of complications and recurrence; however, only a small number of patients was included in this trial.…”
Section: Introductionmentioning
confidence: 99%
“…1), with an average of 13% (Table 4), but has a higher incidence of complications [1,3,4,8,[12][13][14][15][20][21][22] and cost. Zubowicz et al estimated surgical management of patients costs 120,000 US dollars per 100 patients [29].…”
Section: Discussionmentioning
confidence: 99%